2018
DOI: 10.1080/19420862.2018.1505178
|View full text |Cite
|
Sign up to set email alerts
|

Multi-angle light scattering as a process analytical technology measuring real-time molecular weight for downstream process control

Abstract: For many protein therapeutics including monoclonal antibodies, aggregate removal process can be complex and challenging. We evaluated two different process analytical technology (PAT) applications that couple a purification unit performing preparative hydrophobic interaction chromatography (HIC) to a multi-angle light scattering (MALS) system. Using first principle measurements, the MALS detector calculates weight-average molar mass, Mw and can control aggregate levels in purification. The first application us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 18 publications
0
42
0
Order By: Relevance
“…Even for measuring one quality attribute, the combination of multiple sensors might be necessary. For example, the real-time monitoring of the mean molecular weight during a flow-through hydrophobic interaction chromatography (HIC) step for a mAb has been realized by static light scattering and concentration measurements by UV spectroscopy [74]. Because the scattered-light intensity is not only influenced by the molecular weight but by the concentration as well, a concentration measurement is necessary to calculate the molecular weight.…”
Section: Multimodal Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Even for measuring one quality attribute, the combination of multiple sensors might be necessary. For example, the real-time monitoring of the mean molecular weight during a flow-through hydrophobic interaction chromatography (HIC) step for a mAb has been realized by static light scattering and concentration measurements by UV spectroscopy [74]. Because the scattered-light intensity is not only influenced by the molecular weight but by the concentration as well, a concentration measurement is necessary to calculate the molecular weight.…”
Section: Multimodal Spectroscopymentioning
confidence: 99%
“…In recent publications, implemented in-line soft sensors (spectroscopic methods in combination with chemometrics) achieved limits of detection for aggregate and fragment levels below the concentration limits set by the regulatory agencies for drug products [15,45,74]. On a lab scale, Fig.…”
Section: Perspectives For the Biopharmaceutical Downstream Processmentioning
confidence: 99%
“…Multi‐angle light scattering (MALS), refractive index, capacitance, and in‐line UV spectroscopy sensors such as FlowVPE® are some of the key technologies. Patel et al (2018) reported for the first time the use of an in‐line MALS sensor for real‐time monitoring of protein aggregates during downstream purification. The authors demonstrated that automated‐feedback control applied to the purification unit enabled precise control of protein purity in real‐time (Patel et al, 2018).…”
Section: Process Analytical Technologiesmentioning
confidence: 99%
“…Patel et al (2018) reported for the first time the use of an in‐line MALS sensor for real‐time monitoring of protein aggregates during downstream purification. The authors demonstrated that automated‐feedback control applied to the purification unit enabled precise control of protein purity in real‐time (Patel et al, 2018). However, the technology may be challenging to implement in unit operations with significant differences in buffer conductivities and matrices, such as bind‐and‐elute mode purifications.…”
Section: Process Analytical Technologiesmentioning
confidence: 99%
“…Fluorescence spectroscopy has been applied for at-line monitoring of a hydrophobic interaction chromatography step to take pooling decisions and separate correctly folded from misfolded protein [64]. Light sca ering has been employed to monitor protein refolding and aggregation of a fusion protein [65] and to take pooling decisions and separate aggregates from the mAb product [66].…”
Section: Chapter 3 Current Practices and Future Possibilities In Dowmentioning
confidence: 99%